1999
DOI: 10.1007/s004360050677
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis in animal handlers

Abstract: The present study investigated whether people working closely with animals were at higher risk of getting infected with Blastocystis hominis. The prevalence of the parasite was determined in two population groups, i.e., animal handlers and normal healthy individuals who did not work with animals. In all, 105 stool samples were collected from animal handlers from 2 local research institutions, a local zoo, and a local abattoir and 163 stool samples were collected from normal healthy individuals residing in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 6 publications
5
61
0
4
Order By: Relevance
“…21 The individuals who are exposed to animals were shown to have significantly higher rates of blastocystosis. 11,42 However, similar to our findings, a study found no statistical significance between the prevalence of blastocystosis and contact with animals. 15 Previous studies indicated that factors associated with living in the rural regions significantly influence the prevalence of Blastocystis and other parasitic infections.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…21 The individuals who are exposed to animals were shown to have significantly higher rates of blastocystosis. 11,42 However, similar to our findings, a study found no statistical significance between the prevalence of blastocystosis and contact with animals. 15 Previous studies indicated that factors associated with living in the rural regions significantly influence the prevalence of Blastocystis and other parasitic infections.…”
Section: Discussionsupporting
confidence: 80%
“…Numbers of female and male participants were 143 (62.2%) and 87 (37.8%), respectively. Distribution of the individuals according to the age groups was nine (3.9%) for age 7-19, 76 (33%) for age 20-39, 90 (39.1%) for age [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], and 55 (24%) for age 60 and above. A minority of the participants (24%) were university graduates; however, most of the individuals (91.7%) had middle or high socioeconomic status.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by several studies (14,31,32) confirming that animal and food handlers are more likely to be infected. Recently, diagnostic PCR using known sequenced-tagged site (STS)-specific primer sets was developed to distinguish and classify Blastocystis populations into seven different subtypes based on genomic similarity (47,48,50).…”
supporting
confidence: 68%
“…In previous studies using Jones' medium supplemented with 10 % horse serum (Salim et al 1999 ;Leelayoova et al 2002 ;Suresh and Smith, 2004 ;Termmathurapoj et al 2004 ;Yakoob et al 2004 ;Yoshikawa et al 2004 c), only human faecal samples were screened for Blastocystis. However, several different types of media to cultivate Blastocystis have been reported, and it has been suggested that the usefulness of cultivation may depend on the reagents and protocols employed (Zaman and Khan, 1994 ;Leelayoova et al 2002).…”
Section: Discussionmentioning
confidence: 99%